Multi Attribute Content Distribution and Replication Based Video Streaming in Wireless Networks for Qos Improvement - Balakrishnan, A.; Thenmozhi, N. (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
The growth of information technology has introduced various functionalities and services to support video streaming like video streaming and live streaming. There are many approaches has been discussed to support content delivery in wireless networks, but suffers with the problem of latency and quality of streaming which takes more time and the frequency of retransmission is high. To solve these problems, we propose a multi attribute location selection and distribution approach to select the location from where the video content has to be fetched and based on the multi attribute replication scheme new copy of the video content will be replicated in more locations according to various factors of quality of service. The proposed method maintains number of replicas of video content in different locations of wireless networks. The method selects the location of the video content or the node which has the requested data according to the delay present in the network and the user location. Also the number of replicas maintained is performed according to the spatial request factor which represents the number of request being received from different user from a specific spatial region and the other factors like delay, number of users and the traffic incurred in the network towards a video content. The proposed method reduces the overall latency present in the network and increases the efficiency of content delivery which supports multimedia data transfer. Also the proposed method reduces the overall time complexity and reduces the overhead introduced by data transfer.